THE VOICE OF THE CHILD: EXPERIENCES OF CHILDREN, IN MIDDLE CHILDHOOD, REGARDING CHILDREN’S COURT PROCEDURES - Claasen, Louie Talitha; Spies, Gloudina Maria (Social Work/Maatskaplike Werk, 2017)
<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Current statistics show an alarming number of children entering the South African children’s court system annually. Yet little to no research has been conducted directly with the children who actually attend children’s courts within the South African context, specifically since the promulgation of the new Children’s Act 38 of 2005. The research reported here, using one-on-one semi-structured interviews, highlighted the voices of the children regarding their experiences of children’s court procedures. Results indicated that, because of a lack of preparation, the majority of children experienced children’s court procedures negatively. Recommendations for a children’s court-specific preparation programme are made